Round cell sarcoma with CIC‐DUX4 gene fusion: Discussion of the distinctive cytomorphologic, immunohistochemical, and molecular features in the differential diagnosis of round cell tumors. Issue 5 (22nd January 2016) - Chebib, Ivan; Jo, Vickie Y.
Abstract : BACKGROUND: Undifferentiated round cell sarcomas are a heterogeneous group, and include tumors that resemble the Ewing sarcoma family. Although a subset defined by recurrent CIC‐DUX4 gene fusion has been recently characterized, data regarding the cytomorphologic features are currently limited. Two recent fine‐needle aspiration (FNA) cases prompted review of the spectrum of round cell tumors in the differential diagnosis to determine distinctive diagnostic features. METHODS: Two genetically confirmed FNA cases were identified. Cytomorphologic features were evaluated on FNA smears and hematoxylin and eosin‐stained cell block and concurrent needle biopsy sections, and immunohistochemical studies performed on cell block and biopsy sections were reviewed. RESULTS: The 2 patients were a 24‐year‐old man with a posterior mediastinal mass and a 69‐year‐old woman with a gluteal mass. FNA smears were cellular with tumor cells present in large groups and singly dispersed. Tumor cells had large, round‐to‐ovoid, hyperchromatic nuclei with irregular membranes, frequent large nucleoli, and a moderate amount of vacuolated cytoplasm. Both cases demonstrated necrosis, and one case had prominent myxoid stroma. Immunohistochemistry demonstrated focal‐to‐multifocal CD99 positivity and diffuse nuclear staining for WT1; staining for cytokeratin, desmin, S‐100, CD34, CD45, and TdT were negative. Fluorescence in situ hybridization demonstrated CIC‐DUX4 fusion in both cases. CONCLUSIONS: CIC‐DUX4 round cell sarcoma differs from Ewing sarcoma in that it has more atypical cytologic features and lacks the diffuse membranous CD99 staining pattern characteristic of Ewing sarcoma. The differential diagnosis is broad, and requires the judicious use of ancillary studies. Focal‐to‐multifocal CD99 immunoreactivity and diffuse nuclear WT1 positivity is characteristic of CIC‐DUX4 sarcoma, and should prompt molecular testing. Cancer Cytopathol 2016;124:350–61 . © 2016 American Cancer Society . Abstract : A subset of undifferentiated round cell sarcomas is now known to be characterized by CIC‐DUX4 gene fusion, and may be difficult to distinguish from Ewing sarcoma and other round cell tumors. The cytomorphologic, immunohistochemical, and molecular features with attention to the challenging differential diagnosis are herein reviewed.